ANALYSIS OF HYPERTENSION INCIDENCE IN PRODUCTIVE AGE GROUP AT PLAJU HEALTH CENTER PALEMBANG CITY - Prathama, Grease; Harokan, Ali; Ekawati, Dianita; Yusnilasari (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Hypertension is a non-communicable disease with increasing prevalence, particularly among the productive age group. Lifestyle factors and family history are suspected to significantly contribute to the incidence of hypertension. This study aimed to analyze the association between various risk factors and the incidence of hypertension in individuals of productive age. This was a cross-sectional study involving 375 respondents aged 15–59 years registered at Plaju Public Health Center. Samples were selected using accidental sampling. Data were collected using questionnaires, blood pressure measurements, and metabolic status assessments. Data analysis included univariate, bivariate (Chi-Square test), and multivariate (logistic regression). Bivariate analysis revealed significant associations between several factors—including education, family history of hypertension, sodium intake, physical activity, BMI, smoking, cholesterol, and stress—with hypertension. Logistic regression identified sodium intake as the most dominant factor influencing hypertension. The regression model demonstrated strong predictive ability. Hypertension among the productive age population is influenced by a combination of lifestyle and genetic predisposition. Controlling sodium intake, promoting healthy lifestyles, and conducting routine screening are essential for hypertension prevention in this age group.